Knowledge, attitude, and practices of thalassemia amongst urban community members: a cross-sectional study - Shami, Besher; Khalid, Rameen; Kamran, Abdullah Bin; Khalid, Muhammad Ahmad; Shahzad, Farhan; Rehman, Muhammad Ebad ur; Asif, Omaima; Shahzad, Faizan; Khan, Hamza (International Journal Of Community Medicine And Public Health, 2025)
Background: Thalassemia is a global health concern due to its high prevalence and the absence of a cure. Around the world, there are approximately 100 million carriers of beta-thalassemia, with roughly 100,000 of them being children. A KAP study on thalassemia can provide valuable insights into the perceptions, and behaviors of Pakistani individuals, communities, or healthcare professionals related to the disease. Methods: We conducted a descriptive cross-sectional study in Rawalpindi, Pakistan. After taking consent, data was collected from 368 individuals, through a mixed-mode questionnaire that was administered both online and in person, from July 2nd, 2023 to August 30th, 2023. Data was collected and cleaned in excel and then imported into IBM® SPSS v27 statistical package. Results: Data was gathered from 368 individuals with 168 (43.8%) males and 206 (55.7%) females. The mean age of the participants was 34.57±13.19. Independent Samples T-test showed no significant difference in KAP Scores between both genders (p= 0.448). One-way ANOVA showed significant differences among different education level (F-statistic= 40.45, p=0.02). Lastly, bivariate correlation analysis between Age and KAP Scores showed a negative weak correlation (Coeff. = -0.25, p= 0.01). Conclusions: The population mean scores for knowledge were 5.95±3.200 out of 12, for attitude, 6.40±2.032 out of 10, and for 3.49±1.526 out of 6. Higher Education led to higher KAP scores. Lastly, age was seen to negatively affect KAP scores, with higher KAP scores pertaining to thalassemia seen in younger individuals.